2020
DOI: 10.1111/sum.12651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polymer materials on the transformation and utilization of soil nitrogen and yield of wheat under drip irrigation

Abstract: Nitrogen management is the key to improve crop yield. Polymer materials are widely used as water-retaining agents in agriculture, but little is known about how polymer materials affect the transformation and utilization of soil nitrogen. This study focused on the effects of three polymer materials (humic acid extracted from cottonseed meal, H; modified polymer prepared by using polyacrylamide as main raw material, P; and composite polymer material composed of humic acid and modified polymer, HP) on the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Studies have demonstrated that water retention agents can retain soil nutrients and promote nutrient uptake by plants [23,24]. In this experiment, the contents of soil alkali-hydrolyzed nitrogen, available phosphorus and available potassium of each treatment with water retention agent were significantly higher than those of the control at the anthesis stage of wheat, indicating that the application of water retention agent can preserve soil nutrients and reduce nutrient loss before the anthesis stage of wheat [25].…”
Section: Soil Nutrientsmentioning
confidence: 55%
“…Studies have demonstrated that water retention agents can retain soil nutrients and promote nutrient uptake by plants [23,24]. In this experiment, the contents of soil alkali-hydrolyzed nitrogen, available phosphorus and available potassium of each treatment with water retention agent were significantly higher than those of the control at the anthesis stage of wheat, indicating that the application of water retention agent can preserve soil nutrients and reduce nutrient loss before the anthesis stage of wheat [25].…”
Section: Soil Nutrientsmentioning
confidence: 55%
“…It was found that the NH 4 + -N enrichment concentration in paddy soil with HCAP treatments was higher than that for the CKU, which illustrated that NH 4 + -N (1.6- to 6.0-fold) in the HCAP treatments was easily enriched by the paddy soil due to the higher humic acid content of the HCAPs. A previous study also demonstrated that the addition of humic acid enhanced the immobilizations of soil TN and NH 4 + -N . Hence, paddy soil enriched N-containing components due to the strong complexation with soil constitutions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nutrient supply is also a key factor influencing the growth of plants. It has been reported that PVA can enhance the ability of plants to absorb nitrogen [155]. This explains the better growth of plants treated with PVA.…”
Section: Promotion Of Vegetation Growthmentioning
confidence: 89%